Plurality of places of provision of services in the contracts for the carriage of persons and goods - Paredes Pérez, José Ignacio (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The aim of this research is the analysis of the problems of interpretation and application linked to the special jurisdictional rule in matters relating to a contract foreseen in article 7 (1) b) of Regulation 1215/2012, on the basis of the main changes provided by Judgments of the Court of Justice Flightright GmbH and Zurich Insurance Plc in the framework of contracts for the carriage of persons and goods. On these judgments, the CJEU provides a wide interpretation regarding the definition of the notion of contractual matter, in order to include in this definition the claims for compensation brought by passengers affected against a non-contractual air carrier by the loss of a second connection flight due to the delay of the first flight operated by the sued company. Likewise, the CJEU makes a wide interpretation of the letter b) of the mentioned article for identifying, according to the nature of the contract, the two main obligations linked to the essential elements of both types of contracts.